Effects of replacing soybean meal with high-protein dried distillers grains with solubles on growth performance, carcass characteristics, and carcass fat quality in finishing pigs - D L Goehring; J L Usry; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 204 barrows and gilts (PIC, 337 × 1050, initially 129.6 lb) were used in a 73-d study to determine the effects of replacing soybean meal (SBM) with high-protein dried distillers grains with solubles (HPDDGS) on growth performance, carcass characteristics, and carcass fat quality in finishing pigs. Pens of pigs (3 barrows and 3 gilts per pen) were randomly allotted by initial BW to 1 of 4 treatments with 8 or 9 replications per treatment. All pigs were fed diets with 15% HPDDGS for 10 d prior to the start of the study. Treatments included: (1) corn-soybean meal diet with 0.15% crystalline lysine, (2) HPDDGS and crystalline amino acids replacing 50% of the SBM in diet 1, and two diets in which 100% of the SBM was replaced by either: (3) HPDDGS and a high amount of crystalline amino acids or (4) a high amount of HPDDGS and low levels of crystalline amino acids. Diets with low amounts of crystalline amino acids (Treatment 4) contained 10% more HPDDGS to replace SBM than diets with high amounts of crystalline amino acids (Treatment 3). Diets were fed in three 28-d phases (130 to 180 lb, 180 to 240 lb, and 240 to 280 lb) for Phases 1, 2, and 3, respectively. Diets 1 and 3 in all phases were blended (50:50) via the FeedPro system (Feedlogic Corp., Willmar, MN) to make diet 2. Overall, replacing 50% of the SBM with HPDDGS and crystalline amino acids had no effect on growth performance; however, replacing 100% SBM with HPDDGS and crystalline amino acids resulted in decreased (P<0.02) ADG and ADFI but no difference (P>0.75) in F/G. In the two diets where 100% of the soybean meal was replaced with HPDDGS, the amount of added crystalline amino acids had no effect on growth performance.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Amino acids; High-protein DDGS; Finishing pig